Cumulative Effects of Industrial Development and Treaty 8 Infringements in Northeastern British Columbia: The Litigation Yahey v. BC (S151727) – Case Comment - Amatulli, Giuseppe (Arctic Review on Law and Politics, 2022)
On June 29, 2021, the BC Supreme Court issued the verdict of the Yahey v. British Columbia litigation (S151727). For the first time in Canadian legal history, a First Nation Band (BRFN – BlueBerry River First Nation) sued a provincial Government for the cumulative effects of industrial development intertwined with Treaty 8 infringements. The proceeding lasted for six years (2015–2021), with more than 160 days of trials and dozens of hours of affidavits sworn, and it resulted in a ground-breaking verdict. The Court recognised that in authorising industrial development, the Province had been unable to consider and deal with the cumulative impacts that projects had on the traditional lifestyle of BRFN members, besides breaching its obligation to BRFN under Treaty 8. This comment argues that by recognising that the Province cannot continue to authorise activities that breach Treaty 8 and Section 35 of the 1982 Constitution, the verdict may pave the way to a real implementation of the FPIC (Free, Prior and Informed Consent) in the BC legal framework. The ruling provides that the BC Government and the Band engage in meaningful consultation and negotiation to enforce mechanisms to assess and manage cumulative effects on the BRFN traditional territory. The parties were given six months to negotiate based on the litigation outcomes. On October 7, 2021, a preliminary agreement between the BRFN and the BC Province was signed. Important issues had been addressed throughout the trial. From confidentiality and the duty to consult in good faith to the constitutionality of Court hearing fees and the possibility to obtain other kinds of injunctions until the trial; the outcomes of this litigation may well be considered as a milestone to advance the Canadian legal framework, further recognising essential rights of Canadian Indigenous peoples in terms of Constitutional, social, and environmental justice.